Viabilidad de la recuperación de plusvalías en México: el caso del municipio de Monterrey - Almanza Rueda, José Luis; Fitch Osuna, Jesús Manuel (El Colegio de México A.C., 2023)
The objective of this research is to determine the viability of capital gains recovery as a financial instrument for urban infrastructure in the city of Monterrey. It identifies the current situation of the phenomenon, as well as a case study that allows identifying the theoretical and methodological findings that contribute to understanding it in Monterrey, Nuevo León, Mexico. The conceptual and theoretical arguments reviewed are the urban economy, urban financing, urban infrastructure and the recovery of capital gains. Subsequently, an analysis of the change in the value of land in neighborhoods of that municipality, in order to visualize the evolution of the value and thereby identify the differences in capital gains generated and determine which are the factors that affect the value of the land to a greater extent. Those are categorized into two dimensions of analysis: Land value and accessibility. Finally, the main findings are described, among which are only the access to mass public transport and the correlation between the appreciation of the neighborhoods before it.